KOMPARASI KINERJA SAHAM PT UNILEVER INDONESIA TBK SEBELUM DAN PADA SAAT PANDEMI COVID-19 (PERIODE TAHUN 2017-2022) - Didi Rahmat; Sukma Febrianti; Imam Suharto (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2023)
PT Unilever is one of the leading companies in Indonesia, which has become an attraction to invest in the company. The Covid-19 pandemic caused all business sectors to have a downtrend impact, as did the Unilever company, whose share price fell quite deeply during the pandemic. Using an Independent T-test sample, this study will examine differences in Unilever stock performance before and during the Covid-19 pandemic. The test result shows that there is a significant difference in Unilevers stock performance before and during the Covid-19 pandemic.